Technology roadmapping in security and defence foresight. Issue 6 (12th November 2018) - Vicente Oliva, Silvia; Martinez-Sanchez, Angel
Abstract : Purpose: This paper aims to provide an analysis of Spanish Defence National Foresight Exercise. Design/methodology/approach: The analysis is based on a content analysis of public domain Spanish Defence National Foresight Exercise, and a study directed to analyse the impact on defence technological and industrial base. Findings: Foresight studies on the defence and security environment uses hybrid methodologies, but rarely involve all the stakeholders, and specially the citizens. The authors place a particular emphasis on the impact of these defence and security foresight studies, and following policies to increase the competitiveness and advanced technologies in the future. The analysis of the Spanish contractors allows an evaluation of the roadmaps as a policy instrument for the industrial defence industry. The main challenges for the next exercises in the European countries are to increase the interest in the firms' intelligence systems, and the participation and representation of citizens as a way to guarantee their rights. Therefore, a technology roadmap must be complemented with other more participative foresight methods. Originality/value: Foresight studies on the defence and security environment have been the subject of very few systematic analyses of impact. This paper makes a contribution to such analysis.